Different Techniques to Establish Occlusal Anatomy of Posterior Teeth with Composite. A Review - Lora Mishra1, Gathani Dash2, Shashireka Govind3, Siba Prasad Jena4, Satabdi Pattanaik4, Manoj Kumar5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Composite resin restoration on posterior teeth through the incremental technique is, generally, a timeconsumingprocedure with the risk of contamination between the layers. Therefore, there is a need tofacilitate the work of dental professionals and achieve aesthetic and functional results such as the occlusalstamp technique. “Stamp technique” is a technique used for restoring class I and class II restorations withaccurate occlusal topography. It was introduced mainly to restore Class I cavities and erosively damagedteeth. A stamping technique is an easy-to-follow procedure to recreate accurate occlusal topography for adirect composite resin restoration effectively and efficiently with less time needed for finishing and polishingof the restoration. This technique consists of fabricating an occlusal matrix that mimics the natural occlusalanatomy of posterior teeth,before cavity preparation takes place. This matrix is then pressed against thefinal composite increment before curing takes place and is suitable in cases where caries is evident duringthe clinical examination or radiographically within tact marginal ridges and ideal occlusal anatomy. Forovercoming the main disadvantage of polymerization shrinkage seen in composite restorations, it has [tobe done using incremental layer technique. Stamp is used in the final layer to replicate the natural anatomyof the occlusal surface. A precise tooth-like restoration having an accurate functional occlusion is obtainedwhen the stamp technique is performed. This technique also can be utilized for class II cavity restorationswhere the marginal ridge is intact. This case report describes simple class I composite restoration usingstamp technique. The main objective is to replicate occlusal anatomy by making a copy of the originalunprepared tooth structure to get a perfect anatomy in a few minutes. This review walks through manytechniques utilized for simulating posterior occlusal anatomy.